Role of Nurses in Cancer Education, Screening, and Detection in the Community: Narrative Review Addressing the Existing Lacunae and Scope in India - Baliga, Manjeshwar S.; Kalaimathi, Anigrace; Jagadeesh, Nalini S.; Ullal, Chandani; Rajeev, Antappa G.; Krishna, Abhishek; Simon, Paul; George, Thomas; Palatty, Princy L. (Indian Journal of Medical and Paediatric Oncology, 2025)
Across the world, nurses are an important component in both patient and community health care and are excellent ambassadors for community education and awareness endeavors. Cancer is on a rise and creating awareness on the causes, signs, and inculcating the importance on timely detection and accordingly an early treatment-seeking behavior can be very useful in reducing the incidence and can contribute to decreasing the morbidity and mortality associated with the ailment. Effective and correct education play a crucial role in community awareness and nursing interventions in tobacco cessation counselling and cervical cancer screening have been documented from across the world. Efforts to improve the community knowledge, advocacy for cancer screening, and the development of new technologies for cancer screening will allow for improvements in cancer screening over time. This need-of-the-hour narrative review addresses the role nurses can play in cancer education, screening, and detection in the Indian community. In addition to this, the existing lacunae and ways to fill the gap for the betterment of the fraternity and the society at large are also addressed. It is expected that this review, which is the first on the topic from India, will benefit the fraternity and the society at large.
Keywords: cancer awareness; screening; community; education; nurses